The effect of CSR on the financial performance of Islamic banks in the Middle East: The moderating role of ownership concentration and type - Alarabeyyat, Ahmad Abed Alhaleem Ahmad; Kadir, Mohd Rizuan Abdul; Kamarudin, Khairul Anuar; Sapingi, Raedah Bte.; Al-Dalaien, Ahmad (Edelweiss Applied Science and Technology, 2025)
Corporate Social Responsibility (CSR) practices are widely practiced in banks globally. It is deemed more crucial for Islamic banks (IBs) since their establishment is related to the Shariah principle and social justice. However, the approach to implementing CSR differs as they have integrated CSR through Shariah compliance and ethical mandates compared to conventional banks that adopt formalized strategies embedded in their corporate structure. The study is designed to explore the effect of CSR on the IB's performance and the moderating effect of ownership concentration on this relationship in the Middle East. Using samples of Islamic banks in nine countries from 2012 to 2012, a total of 58 IBs were selected. The findings showed that CSR positively affected the ROE and Tobin’s Q but not the ROA. In addition, ownership concentration has a higher effect on the ROA of less concentrated banks, while the effect of CSR on ROE and Tobin’s Q is higher in concentrated banks. This relationship between CSR and ROE and Tobin’s Q is stronger in public banks compared with private banks. This finding suggests that the Middle East IBs should boost CSR implementation through more formalized guidelines since it could enhance their region's market reputation and financial health. However, more studies are still needed to explore the other determinants of a bank’s performance.